2012
DOI: 10.3357/asem.3201.2012
|View full text |Cite
|
Sign up to set email alerts
|

Altitude Decompression Sickness Incidence Among U-2 Pilots: 1994-2010

Abstract: DCS remains prevalent among U-2 pilots. An increase in number and severity of cases correlated temporally with increased operational tempo of the U-2 squadron. Changes in cockpit pressurization and limiting the length and frequency of hypobaric exposure may reduce future incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…2 The risk of DCS per flight increased from 0.076% pre-2006 to 0.23% during the 2006-2010 operation years, believed to be related to more frequent and longer periods of exposure for the pilots. 3,4 Importantly, 44% of episodes were diagnosed as NDCS, with symptoms ranging from mild, such as complaints of slowed thought processes, to severe, including anomia, confusion, unresponsiveness, 5 and permanent cognitive decline. 6 We previously reported that clinical NDCS was associated with an increase in white matter hyperintensities (WMH).…”
mentioning
confidence: 99%
“…2 The risk of DCS per flight increased from 0.076% pre-2006 to 0.23% during the 2006-2010 operation years, believed to be related to more frequent and longer periods of exposure for the pilots. 3,4 Importantly, 44% of episodes were diagnosed as NDCS, with symptoms ranging from mild, such as complaints of slowed thought processes, to severe, including anomia, confusion, unresponsiveness, 5 and permanent cognitive decline. 6 We previously reported that clinical NDCS was associated with an increase in white matter hyperintensities (WMH).…”
mentioning
confidence: 99%
“…3 In response to an increased incidence of NDCS in the United States Air Force (USAF), 4,5 research was performed that demonstrated pilots who experienced NDCS had increased volume and number of subcortical T2-weighted white matter hyperintensity (WMH) abnormalities. 6 Follow-up research reported significant elevation of WMH in high-altitude pilots without clinical symptoms of NDCS.…”
mentioning
confidence: 99%
“…The closest analogue to EVA is high-altitude U-2 plane pilots, a US Air Force spy plane dating back to the 1950s. While the published operating altitude of the U-2 is 70,000 ft, partial cabin pressurization exposes pilots to prolong periods of 29,500 ft while breathing 100% O 2 (Hundemer et al 2012), an environment similar to astronauts during EVA. Another acceptable surrogate population but without the added potential of radiation exposure are the inside safety monitors for altitude chamber training who are repetitively exposed to brief (< 30 min) nonhypoxic hypobaria (25,000 ft).…”
Section: White Matter Hyperintensities (Wmh)mentioning
confidence: 99%